2015
DOI: 10.1080/09687599.2015.1093461
|View full text |Cite
|
Sign up to set email alerts
|

The identities and social roles of people with an intellectual disability: challenging dominant cultural worldviews, values and mythologies

Abstract: Intellectual disability is commonly conceptualised as stigmatised identity with which one has to live. However, within the literature the notion of a damaged identity is contested. The aim of this research was to explore the social construction of intellectual disability, with an emphasis on the identities and social roles of people with an intellectual disability. Informed by a contextualist perspective, this research was conducted within a participatory framework. The co-researchers involved in this research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
0
23
0
2
Order By: Relevance
“…Further, such statements echo results from Dorozenko, Roberts, and Bishop's (2015) study in which staff working with adults with intellectual disability framed individuals identities in terms of agency and ability rather than deficit and incompetence.…”
Section: Children: Not Children With Autismmentioning
confidence: 57%
“…Further, such statements echo results from Dorozenko, Roberts, and Bishop's (2015) study in which staff working with adults with intellectual disability framed individuals identities in terms of agency and ability rather than deficit and incompetence.…”
Section: Children: Not Children With Autismmentioning
confidence: 57%
“…Upon much reflection, we have concluded that we are undoubtedly the main beneficiary of this research. I have obtained data to complete my PhD, had the opportunity to present the research at two international conferences, and we have published about the process (Povee et al, 2014) and outcomes (Dorozenko et al, 2014) of the research. I also feel that throughout the research project, I…”
Section: Who Gains From the Research?mentioning
confidence: 99%
“…Causal layered analysis (Inayatullah, 1998), an indepth, multilevel analysis that enables the factors that perpetuate social issues to be identified through the interaction of several different levels of understanding, was used to analyse both the Member and staff interview data. For a detailed description of the research process and a summary of the research findings, please see Povee, Bishop, and Roberts (2014) and Dorozenko, Roberts, and Bishop (2014).…”
Section: The Researchmentioning
confidence: 99%
“…In particular, the classification of intellectual disability has been described as a "deeply devalued social category" (Dorozenko et al, 2015(Dorozenko et al, , p. 1346, the worst diagnosis that a child could receive (Knight, 2013), and the label most despised and avoided (Lalvani, 2015). It is clear that this is a label that has the potential to be profoundly stigmatising, and indeed, research suggests this is so.…”
Section: Negative Consequences Of Labellingmentioning
confidence: 99%
“…It is widely accepted that people with disability are at risk of leading impoverished lives (Harley, Mpofu, Scanlan, Umeasiegbu, & Mpofu, 2015). To further categorise someone as having an intellectual disability puts people at an even greater risk of being stigmatised (Dorozenko, Roberts, & Bishop, 2015) and treated badly (Emerson, 2013). Described as "disregarded", "incapable", "forgotten" (Lyons & Cassebohm, 2012, p. 80), individuals with intellectual disability have long been subject to marginalisation (Burrell & Trip, 2011) and damaging service responses such as segregation and congregation (see, for example, Blatt & Kaplan, 1974).…”
Section: Overview Of the Thesismentioning
confidence: 99%